UTILIZATION OF CORN GERM AND SUNFLOWER SEEDS AS A NEW SOURCES OF LECITHINS AND THEIR MODIFIED FORMS IN MANUFACTURE OF CARAMEL - Y Kishk; Salwa Abo-El-Fetoh (Arab Universities Journal of Agricultural Sciences, 2005)
Fractionation and acylation by ethyl alcohol and acetic anhydride were carried out to produce a modified corn germ and sunflower lecithins from their crude leci-thins. Emulsification activity and emulsion stability indices (EAI & ESI) were de-termined at different pH values (2, 4, 6, 8 and 10) for commercial and studied leci-thins. EAI was significantly improved in modified lecithins in comparison to crude lecithins with increasing rate of 52.9 and 58.6 % for corn germ and sunflower etha-nol soluble fraction lecithins and 15.6 and 20.5 % for acylated corn germ and sun-flower lecithins, respectively. The changes in ESI after times of 20, 40 and 60 min. showed a higher stability of emulsions prepared using modified lecithins which were closed to that prepared using commercial soy lecithin. Caramel was prepared using commercial soy, corn germ, sunflower lecithins and their modified forms. Hardness of tested samples was determined in the start of storage time while, acid value, per-oxide value, fatty acid pattern and sensory attributes were determined during storage period at room temperature for six months. Data revealed insignificant difference in caramels hardness. Samples contained crude sunflower; acylated corn germ and sun-flower lecithins were more sensitive to oxidation while, those prepared using com-mercial soy, crude corn germ, ethanol soluble fraction of corn germ and sunflower lecithins showed higher oxidative stability with significant differences (P<0.05). Concerning sensory evaluation, both ethanol soluble fractions and acylated lecithins produced high quality caramels not differed (P>0.05) to control one that contained commercial soy lecithin. The quality and quantity of lecithin that used in prepared of caramel samples played a major role in their characteristics. The modified corn germ and sunflower lecithin forms were preferred than the raw lecithins owing to their higher emulsifying activity and lesser quantity used. The ethanol soluble lecithins fraction, especially of corn germ can be competitive to the commercial soy lecithin in all emulsified food products.